The covering problem for finite rings with respect to the RT-metric - Yildiz, Bahattin; Siap, Irfan; Bilgin, Tevfik; Yesilot, Gursel (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this work, the cardinality of the minimal R-covers of finite rings with respect to the RI-metric is established. By generalizing the result in Nakaoka and dos Santos (2010) 111, the minimal cardinalities of 0-short coverings of finite chain rings are calculated. The connection between R-short coverings of rings with respect to the RT-metric and the 0-short coverings of rings is demonstrated, and with the help of this connection, the problem of finding the minimal cardinalities of R-short coverings of finite chain rings is solved. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: RT-metric; 0-short covering; Covering; Short covering; R-balls; CODES; Mathematics